Impact of pyrethroids on methane digestion = Wpływ pyretroidów na proces fermentacji metanowej - Sadecka, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The process of methane digestion is very sensitive to any changes in the environment. In the group of compounds exerting a toxic effect on the process a special notice should be taken to pesticides - agricultural chemicals, set purposely into the environment to destroy both animal and floral parasites.
Keywords: pestycydy; perytroidy; fermentacja metanowa; pyrethroids; methane digestion process; sewage sludge